2006
DOI: 10.1016/j.arthro.2005.09.025
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Properties of an Osteochondral Cylinder Graft-Recipient Construct on Autologous Osteochondral Transplantation

Abstract: Care should be taken when planning the rehabilitation program at an early phase after osteochondral transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…We previously reported decreased stiffness at postoperative weeks 1, 3 and 8 compared to normal cartilage stiffness. The stiffness at postoperative week 3 was the lowest, suggesting that subchondral bone formation and remodelling influences the changes of cartilage stiffness [14] and similar results were found in this study; that is, the stiffness of the transplanted grafts decreased the most at postoperative week 3 in Group III. At postoperative week 3, the average stiffness in Group I was significantly greater than that in Group III.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We previously reported decreased stiffness at postoperative weeks 1, 3 and 8 compared to normal cartilage stiffness. The stiffness at postoperative week 3 was the lowest, suggesting that subchondral bone formation and remodelling influences the changes of cartilage stiffness [14] and similar results were found in this study; that is, the stiffness of the transplanted grafts decreased the most at postoperative week 3 in Group III. At postoperative week 3, the average stiffness in Group I was significantly greater than that in Group III.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, changes in the mechanical properties of the transplanted osteochondral graft have been analysed in various autologous osteochondral transplantation models and evaluated at various periods after surgery [9,10,15,28]. We previously demonstrated that the structural properties of an osteochondral cylinder-graftrecipient construct immediately after surgery are not significantly different from those of normal cartilage and that the structural properties of an osteochondral cylindergraft-recipient reconstruction are significantly worse at postoperative weeks 1 through 8 than in normal cartilage [14]. We speculated that changes in the structural properties of the transplanted osteochondral graft are influenced by the healing process at the subchondral bone level.…”
Section: Introductionmentioning
confidence: 99%
“…This has been proven in rabbit, ovine, and porcine models at time points to as far as 1 year after transplantation. [22][23][24][25][26][27][28] In addition to the knee, osteochondral grafting has been used in the capitellum, talus, and femoral head with graft viability being proven with second-look arthroscopy, MRI, and biopsy. 29 -34 Barber in 1991 showed that osteochondral grafts maintained their integrity, and living chondrocytes and osteocytes in the grafts were found at 12 months after implantation.…”
Section: Discussionmentioning
confidence: 99%
“…23 In multiple studies including rabbit, ovine, and porcine models, chondrocytes and osteocytes of the osteochondral graft have been shown to survive transplantation. [24][25][26][27][28][29][30] Osteochondral grafting has also been used in the capitellum, talus, and femoral head, with graft viability proven with second-look arthroscopy, MRI, and biopsy. [31][32][33][34][35][36][37] The MRI of our patient at 21 months postoperative showed bone incorporation of the graft to the capitate and the presence of graft cartilage (►Fig.…”
Section: Discussionmentioning
confidence: 99%